Alternative of Applet for Digital Signature Long Term Value in Web Based Signing - Pandey, Anup Kumar; Mahto, Anil Kumar (International Journal of Computer Sciences and Engineering, 2019)
Today various type of organizations interact with DATA; while sharing / storing / retrieving / communicating such huge data with Public; such as Government organization, Medical, Agricultures(land records) Insurance domain (in term of storing / archiving data/file) and other try to validate the digital document using digital signature . Some document might be used for a short time period, but here I am talking about sharing / store / archive the document for a longer period i.e. long time value (LTV), because if documents are important for future having future prospective need to be preserved for a longer period than expected. The main problem is how to ensure about, the document authenticity, Integrity, non-repudiation, and proof of existence for long-term. Here we put the document (.pdf) sign, which contains the information’s like (Certificate, certificate chain, signed message digest, revocation information and time stamp), and here also trying to provide the solution for replacement of applet in web based signing, newer approach will be available both for the Standalone as well as window services i.e. Time and Cost saving for the user.